2019
DOI: 10.3390/foods8120631
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Ethanol Extract of Mesquite Leaves to Enhance the Oxidative Stability of Pork Patties

Abstract: The lipid oxidation (LOX) of pork meat has been associated with loss of quality and shorter shelf life. Consequently, synthetic antioxidants have been used to reduce this process, but their use has shown potential health risks. Thus, the use of natural ingredients has been suggested as a strategy to prevent LOX. This study aimed to assess the oxidative stability of pork patties treated with ethanol extract of mesquite leaf (EEML) during storage. Furthermore, the polyphenol composition (TPC, total phenolic, TFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
(69 reference statements)
2
18
0
Order By: Relevance
“…Positive effects were also obtained with the use of ethanolic extracts of mesquite leaves ( Prosopis velutina ). Ramírez-Rojo et al [ 90 ] studied the effect of the extract (0.05 and 0.1%), obtained by UAE (42 kHz/25 °C/30 min) on the preservation of pork patties stored for 10 days at 4 °C. The authors reported that this ethanolic extract could be used to extend the shelf life of meat products, showing a better stability of colour, MetMb, and lipid oxidation during storage.…”
Section: Application Of Plant Extracts In Fresh Meat and Meat Prodmentioning
confidence: 99%
“…Positive effects were also obtained with the use of ethanolic extracts of mesquite leaves ( Prosopis velutina ). Ramírez-Rojo et al [ 90 ] studied the effect of the extract (0.05 and 0.1%), obtained by UAE (42 kHz/25 °C/30 min) on the preservation of pork patties stored for 10 days at 4 °C. The authors reported that this ethanolic extract could be used to extend the shelf life of meat products, showing a better stability of colour, MetMb, and lipid oxidation during storage.…”
Section: Application Of Plant Extracts In Fresh Meat and Meat Prodmentioning
confidence: 99%
“…Ramírez-Rojo et al [ 43 ] reported that mesquite leaf extracts affected the color parameters of pork patties. Initially, the a* values were lower than in the control sample (by 27.8%), and the b* values were higher (by 42.1%) However, after 10 days of storage, the patties treated with extracts displayed the highest redness and the highest yellowness compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…In a study investigating the effect of beef extract on storage stability in rosemary, laurel, eucalyptus, and olive leaves was determined that the mean TBA values of the samples varied between 0.1 and 0.7 mg malonaldehyde/kg (Oğuz et al., 2019). In the study investigated the oxidative stability of pork patties treated with ethanol extract of mesquite leaf during storage was observed TBA values 90% inhibition (Ramírez‐Rojo et al., 2019). Fernandes et al.…”
Section: Resultsmentioning
confidence: 99%